Shenzhen Digital Economy Development Model - Wenbo Lyu; Zhiyao Cao; Jiajun Yin (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
Shenzhen is seizing the strategic opportunity of global innovation resources transfer, focusing on high-end and high-quality scientific and technological innovation resources. Efforts are being made to increase the absorption of top talent, institutions, and advanced technological achievements. Implementation Drum—Encourage the preferential policies for R&D investment of multinational corporations, and actively introduce multinational corporations to the Asia-Pacific region. However, the cost of innovation in Shenzhen is very high, ranking fourth in the country, behind only Guangzhou, Beijing, and Shanghai. Shenzhen’s strategic goal is to build a world-class scientific and technological innovation center with global influence.